Potential evaluation of dry gas by injecting to enhance shale oil recovery under real fracture action - WEI Minzhang; ZHOU Binbin; WANG Chunling; ZHANG Xiaowei; YANG Zhenya (Youqi dizhi yu caishoulu)
In the simulation experiments of dry gas injection in shale， the use of degassed crude oil （the dead oil） in saturated cores and the fracture simplification of cores often lead to discrepancies between experimental simulation and actual field results. A new experimental method for dry gas injection in shale was established by improving the sealing system of the conventional core holder. Hydraulic fracturing was carried out under continued pressure after saturating the core with formation crude oil （the live oil）. Based on the formation of fracture networks， huff and puff experiments of dry gas in the cores were conducted. The huff and puff effect of the live oil and dead oil was compared， and the potential of dry gas injection to enhance shale oil recovery was objectively evaluated. The experimental results show that the cumulative recovery rate of the live oil after five rounds of huff and puff is 49.4%， much higher than that of dead oil at 30.1%. The recovery rate of the live oil in each cycle shows a decreasing trend. In the first three rounds of injection， the gas mainly enhances the crude oil production in the matrix near the fractures through dissolution and expansion， and the cumulative recovery rate of the first three rounds accounts for 82.4% of the total recovery rate. In the subsequent cycles， the gas mainly enhances the production of crude oil in the matrix far from the fractures through diffusion， and the recovery rate of each cycle is relatively low. The area affected by the injected gas can be increased by reducing the interfacial tension between oil and gas and increasing the diffusion coefficient. Using dead oil would significantly underestimate the potential for enhanced oil recovery and gas storage in shale reservoirs.